PENEGAKAN HUKUM TINDAK PIDANA PENGEROYOKAN DI WILAYAH HUKUM POLRES GORONTALO UTARA - Ibrahim, Vicky; Hasan, Yeti S. (Maleo Law Journal, 2024)
The objectives of this study are (1) to find the law enforcement of a criminal act of joint assault by beatings under the Criminal Code (KUHP), and (2) to determine the law enforcement of a criminal act of joint assault by beatings in the jurisdiction of the North Gorontalo Sub-regional Police. This study employs a qualitative research method, which aims at certain objects systematically, correctly, and accurately describing the phenomena that occur in the field. The results of this study indicate that (1) the occurrence of the criminal act of joint assault by beatings in North Gorontalo Sub-regional Police has internal and external factors from the perpetrators themselves, (2) the hard work of the North Gorontalo Sub-regional Police in Preventive/pre-aggressive efforts and repressive efforts in law enforcement against the criminal act of joint assault by beatings. The Preventive/proactive work at the community level and by government agencies is through legal advice or socialization. At the same time, the North Gorontalo Sub-regional Police conducts repression in the form of applicable criminal law. In this article, the effort of the North Gorontalo Sub-regional Police begins with investigation and cooperation with related agencies and leads to the application or enforcement of criminal law, namely Article 170 of the Criminal Code.